Insecticide resisitance in cowpea aphid, Aphis craccivora (koch) and its management - Jangam Hampaiah (Department of Agricultural Entomology, College of Agriculture, 2018)
A study on “Insecticide resistance in cowpea aphid, Aphis craccivora (Koch) and its management” was conducted in College of Agriculture, Vellayani and farmer’s field at Vallamcode, Thiruvananthapuram district during 2016-2018. The main objectives were to assess the insecticide resistance in field population of cowpea aphid, A. craccivora and to evaluate the efficacy of new generation insecticides against resistant population of A. craccivora. A preliminary survey was carried out among major cowpea farmers in Kalliyoor area of Thiruvananthapuram district during 2017-18 revealed the continous use of single insecticide viz., fenvalerate, lambda cyhalothrin, imidacloprid and quinalphos and the occurrence of control failures in the field populations of A.craccivora. Bioassay was carried out in CRD to assess the insecticide resistance in field population of A. craccivora collected from three different locations based on the intensity of insecticide application. A series of concentrations of three insecticides viz. fenvalerate, imidacloprid and quinalphos were prepared in aqueous solution and bio assay was done using F2 generations of aphid populations collected from three locations. Results revealed that population collected from Location-I (Vilavoorkal) was found to be susceptible to insecticides with resistance ratio-1. Population collected from Location- II (Instructional farm, College of Agriculture, Vellayani) was found to be moderately resistant with resistant ratios of 1.67, 2.97 and 2.81 and aphid population collected from Location- III, (Vallamcode) showed more resistance with resistant ratios of 1.71, 19.46 and 7.94 for quinalphos, fenvalerate and imidacloprid respectively. Laboratory experiments were conducted to evaluate the efficacy of new generation insecticides viz. acetamiprid 15 g a.i.ha-1, thiamethoxam 25 g a.i.ha-1, thiacloprid 24 g a.i.ha-1, dinotefuran 25 g a.i.ha-1, thiamethoxam + lambda cyhalothrin 27.5 g a.i.ha-1 and dimethoate (as check ) 200 g a.i.ha-1 against the resistant population of A. craccivora. The result revealed that, significantly higher mortality was observed in A. craccivora treated with thiamethoxam + lambda cyhalothrin 27.5 g a.i.ha-1(100 %) followed by thiacloprid 24 g a.i.ha-1 (91.67 %) and thiamethoxam 25 g a.i.ha-1(90.00 %) which were on par with each other after 3 hours of treatment. Field experiment was laid out in RBD at Vallamcode from where resistant population was collected with four treatments selected from laboratory experiment of aphids. The percent reduction recorded were 97.63, 93.97 and 91.50 respectively in thiamethoxam + lambda cyhalothrin 27.5 g a.i.ha-1, thiamethoxam 25 g a.i.ha-1 and thiacloprid 24 g a.i.ha-1 treated plots at one day after spraying. Dissipation of residues of these effective insecticides was studied by analysing the pods collected at 0, 1, 3, 5, 7 and 10 days after application of insecticides at recommended dose and the result showed that insecticides were dissipated within five days with half-lives of 0.37, 1.73, 1.21 and 4.37 days respectively. The present study revealed the development of insecticide resistance in the field populations of A. craccivora against fenvalerate and imidacloprid. By considering the less mammalian toxicity, good aphicidal activity, consumer safety and high dissipation rate, thiamethoxam 25 g a.i.ha-1 followed by thiamethoxam + lambda cyhalothrin 27.5 g a.i.ha-1 and thiacloprid 24 g a.i.ha-1 could be recommended against A. craccivora in cowpea. Further studies have to be taken up to develop and popularize Insecticide Resistance Management strategies against A. craccivora by giving emphasis on efficient use of insecticides and to conserve the ecosystem for sustainable pest management.